2017
DOI: 10.1093/ons/opw017
|View full text |Cite
|
Sign up to set email alerts
|

Navigation and Image Injection for Control of Bone Removal and Osteotomy Planes in Spine Surgery

Abstract: The intraoperative visualization of resection planes in a microscope's head-up display was found to assist the surgeon during the resection of a complex-shaped bone wedge and may help to further increase accuracy and patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 18 publications
0
34
0
Order By: Relevance
“…Microscope-based AR can be successfully applied in spinal surgery. We had implemented microscope-based AR using commercially available system components 17,18 after the feasibility of microscope-based AR had been shown in a visualization of osteotomy planes 19 and in cervical foraminotomy. 20 In our observational study on 42 patients, AR supported various kinds of spine procedures and facilitated anatomical orientation in the surgical field in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…Microscope-based AR can be successfully applied in spinal surgery. We had implemented microscope-based AR using commercially available system components 17,18 after the feasibility of microscope-based AR had been shown in a visualization of osteotomy planes 19 and in cervical foraminotomy. 20 In our observational study on 42 patients, AR supported various kinds of spine procedures and facilitated anatomical orientation in the surgical field in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…A similar system was also employed in a case of congenital vertebral deformity to accurately define resection volumes and osteotomy planes, in order to acquire a higher degree of precision and surgical safety. 72 Another device used in spine surgery is MicroOptical (Micro-Optical Corp., Westwood, MA, USA): a head-up display used for visualizing intraoperative fluoroscopy during open reduction and internal fracture fixations and spinal pedicle screw placement in a study of 50 cases. The study demonstrated a reduction of surgical time since the surgeon had not to turn away from the patient to view the imaging monitor.…”
Section: Augmented Reality In Spine Surgerymentioning
confidence: 99%
“…Wu et al (45) evaluated the usefulness of AR technology in spine surgery and demonstrated the feasibility and accuracy of the AR system, while the surgeons who participated in the study noted reduced operative time and radiation dose. Kosterhon et al (47) reported the use of AR in a patient with congenital hemivertebra of the thoracolumbar spine, and the system was found useful for the surgeon during the resection of a complex-shaped bone wedge, offering more accuracy and patient safety. Finally, Abe et al (46) dealt with the value of AR technology in percutaneous vertebroplasty.…”
Section: Clinical Studies About the Use Of Augmented Reality In Orthomentioning
confidence: 99%